Structural and dielectric properties of TiO2 thin films grown at different sputtering powers - Akgul, Unal (Springer Heidelberg, 2019)
. TiO2 thin films have been grown by the rf magnetron sputtering technique at different sputtering powers (90, 110, 130 and 150W). The particle size and shape have changed depending on the sputtering power. The XRD results have revealed that the polycrystalline films have a single or mixed phase. The variation in the crystal phase has affected the value of the dielectric constant. The rutile TiO2 thin film has exhibited a higher dielectric constant. The dielectric constant has decreased with increasing frequency.
Keywords: Optical-Properties; Rf-Power; Temperature; Deposition; Pressure; Phase